Treatment strategies, outcomes and prognostic factors in 291 patients with secondary CNS involvement by diffuse large B-cell lymphoma. (April 2018) - El-Galaly, Tarec Christoffer; Cheah, Chan Yoon; Bendtsen, Mette Dahl; Nowakowski, Grzegorz S.; Kansara, Roopesh; Savage, Kerry J.; Connors, Joseph M.; Sehn, Laurie H.; Goldschmidt, Neta; Shaulov, Adir; Farooq, Umar; Link, Brian K.; et al.
Abstract: Purpose: Secondary CNS involvement (SCNS) is a profoundly adverse complication of diffuse large B-cell lymphoma. Evidence from older series indicated a median overall survival (OS) < 6 months; however, data from the immunochemotherapy era are limited. Methods: Patients diagnosed with SCNS during or after first-line immunochemotherapy were identified from databases and/or regional/national registries from three continents. Clinical information was retrospectively collected from medical records. Results: In total, 291 patients with SCNS were included. SCNS occurred as part of first relapse in 254 (87%) patients and 113 (39%) had concurrent systemic relapse. With a median post-SCNS follow-up of 48 months, the median post-SCNS OS was 3.9 months and 2-year OS rate was 20% (95% CI: 15–25). In multivariable analysis of 173 patients treated with curative/intensive therapy (such as high-dose methotrexate [HDMTX] or platinum-containing regimens), age ≤60 years, performance status 0–1, absence of combined leptomeningeal and parenchymal involvement, and SCNS occurring after completion of first-line therapy were associated with superior outcomes. Patients ≤60 years with performance status 0–1 and treated with HDMTX-based regimens for isolated parenchymal SCNS had a 2-year OS of 62% (95% CI: 36–80). In patients with isolated SCNS, the addition of rituximab to HDMTX-based regimens was associated with improved OS. Amongst patients with isolated SCNS in CR following intensive treatment, high-dose chemotherapy and autologous stem cell transplantation did not improve OS (P = 0.9). Conclusions: In this large international cohort of patients treated with first-line immunochemotherapy, outcomes following SCNS remain poor. However, a moderate proportion of patients with isolated SCNS who received intensive therapies achieved durable remissions. Highlights: The overall prognosis of secondary CNS relapse of diffuse large B-cell lymphoma remains poor. Few patients achieve favourable long-term outcomes with current therapies. Younger patients with parenchymal SCNS and no systemic involvement have a relatively good prognosis after intensive therapies. The addition of rituximab to HDMTX-based regimens seems to improve outcomes.